Analisis Hak dan Kewajiban Murid kepada Masyarakat dalam Pandangan al-Qur'an dan Hadits: Studi Buku Lembaga Hidup Karya Hamka - Syaiful Dinata (UIN Kiai Haji Achmad Siddiq Jember, 2023)
This study aims to find out how the rights and obligations of a student to the community are contained in the book “Lembaga Hidup” by Haji Abdul Karim (Hamka). The research is library research, which is qualitative in document study research by analyzing according to the Qur’an and Hadith. The results obtained from this research are the right of a student to the community is to get the right or freedom to live, the right to have opinions and express them in public, the right to broaden the understanding of what he is interested in, the freedom to study, the right to be respected for his stance, the right to be respected for himself and his property or possessions respected, the right to be criticized and to accept or reject criticism from the community. The obligation of society to students is to give them the freedom to live or to society, respect their opinions, expand their understanding to live in society, obliged to give freedom to study, respect the position held by students, and respect their property; it is obliged to give criticism, where the criticism meant here is criticism that builds the quality of a work or self that is being criticized, not dropping the quality or confidence of the recipient of the criticism. These rights and obligations need to be understood, which helps increase the prosperity of social life.